2017
DOI: 10.1089/ars.2016.6810
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 5 Decreases Beta-Amyloid-Mediated Cyclin-Dependent Kinase 5 Activation Through Regulation of Ca2+-Mediated Calpain Activation

Abstract: We found that of the six Prx subtypes, Prx5 was increased the most in cellular (N2a-APPswe cells) model of AD. Prx5 in the brain of APP (amyloid precursor protein) transgenic mouse (Tg2576) was more increased than a nontransgenic mouse. We evaluated Prx5 function by using overexpression (Prx5-WT), a mutation in the catalytic residue (Prx5-C48S), and knockdown. Increased neuronal death and Cdk5 activation by amyloid beta oligomer (AβO) were rescued by Prx5-WT expression, but not by Prx5-C48S or Prx5 knockdown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…We have detected differentially interacting proteins by comparing data sets from the hippocampus and the CA3 subfield of the hippocampus. All the CA3 (PSD95-cTAP; Grik4 Cre) enriched proteins (Abr, Actn4, Bai3, Cacng8, Grik2, Hist1h2al, Mbp, Nlgn3 and Prdx5) have been reported to have important functions in brain that include roles in synapse formation, synaptic plasticity and psychiatric disorders (Duman, Tu, & Tolias, 2016;Ge et al, 2016;Kalinowska et al, 2015;Lanoue et al, 2013;Malty et al, 2017;Martinelli et al, 2016;Oh et al, 2010;Park et al, 2017;Sigoillot et al, 2015;Walikonis et al, 2001;Yamagata et al, 2017). This might indicate that different types of PSD95 complexes exist in different brain regions with distinct functions.…”
Section: Discussionmentioning
confidence: 99%
“…We have detected differentially interacting proteins by comparing data sets from the hippocampus and the CA3 subfield of the hippocampus. All the CA3 (PSD95-cTAP; Grik4 Cre) enriched proteins (Abr, Actn4, Bai3, Cacng8, Grik2, Hist1h2al, Mbp, Nlgn3 and Prdx5) have been reported to have important functions in brain that include roles in synapse formation, synaptic plasticity and psychiatric disorders (Duman, Tu, & Tolias, 2016;Ge et al, 2016;Kalinowska et al, 2015;Lanoue et al, 2013;Malty et al, 2017;Martinelli et al, 2016;Oh et al, 2010;Park et al, 2017;Sigoillot et al, 2015;Walikonis et al, 2001;Yamagata et al, 2017). This might indicate that different types of PSD95 complexes exist in different brain regions with distinct functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that regulation of CDK5 is essential for early neuronal development and differentiation. CDK5 activation, by conversion of p35 to p25, is triggered by calpain activation, which is mediated by intracellular Ca 2+ levels [40]. Here, we studied the effect of CDK5-regulated Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported to have important functions in brain that include roles for synapse formation, synaptic plasticity and psychiatric disorder (Walikonis et al, 2001;Oh et al, 2010;Lanoue et al, 2013;Kalinowska et al, 2015;Sigoillot et al, 2015;Duman et al, 2016;Ge et al, 2016;Martinelli et al, 2016;Malty et al, 2017;Park et al, 2017;Yamagata et al, 2017). This might implicate that different types of PSD95 complexes exist in different brain regions with distinct functions.…”
Section: Discussionmentioning
confidence: 99%